1980
DOI: 10.1016/s0006-3495(80)85074-0
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction observations of chemically skinned frog skeletal muscle processed by an improved method

Abstract: Whole frog sartorius muscles can be chemically skinned in approximately 2 h by relaxing solutions containing 0.5% Triton X-100. The intensity and order of the X-ray diffraction pattern from living muscle is largely retained after such skinning, indicating good retention of native structure in fibrils and filaments. Best X-ray results were obtained using a solution with (mM): 75 K acetate; 5 Mg acetate; 5 ATP; 5 EGTA; 15 K phosphate, 2% PVP, pH 7.0. Equatorial X-ray patterns showed that myofibrils swell after d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
2

Year Published

1983
1983
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 36 publications
6
35
2
Order By: Relevance
“…Low ft relaxing solution contained 1 mM MgCl2, 2 (25 ml) was continuously recirculated with a syringe pump (13 into rigor gradually, usually within 1 hr, although this time was also affected by the gap between the Mylar windows.…”
Section: Methodsmentioning
confidence: 99%
“…Low ft relaxing solution contained 1 mM MgCl2, 2 (25 ml) was continuously recirculated with a syringe pump (13 into rigor gradually, usually within 1 hr, although this time was also affected by the gap between the Mylar windows.…”
Section: Methodsmentioning
confidence: 99%
“…Sartorius muscles from Rana japonica were used. The muscle pair was isolated with pelvic bone attached and was chemically skinned by the method of MAGID and REEDY (1980). The muscle was tied to a glass rod with threads at the pelvic bone and the tibial tendon.…”
Section: Methodsmentioning
confidence: 99%
“…Because of its inability to diffuse into the lattice spacing, dextran could compress the sarcomere and decrease the interfilament distance (Godt and Maughan 1977). Next, it was found that variations in fiber width (as a function of lattice spacing) could be regulated by concentration of dextran (Magid and Reedy 1980). The groups of Moss et al (1983) and Stienen et al (1985) indicated that lattice spacing, rather than length, was responsible for the changes in Ca 2+ -sensitivity in membranepermeabilized skeletal muscles.…”
Section: Interfilament Lattice Spacing Versus Myocyte Lengtheningmentioning
confidence: 99%